Evaluation of bone formation process by dual energy X-ray absorptiometry - MANABE, Masato (Japanese Journal of Oral and Maxillofacial Surgery, 1992)
Evaluation of the osteoinductive potential has been mainly performed by the bone morphometric method or contact microradiogram.However, these methods are much coninlicated and require a long time to prepare the samples.Then, to evaluated the osteoinductive potential of demineralized bone matrix the author used dual energy X-ray absorptiometry which was possible to analyze in situ mineral contents. The pellets about 2 mm thick and 5 mm in diameter of demineralized bone matrix were prepared by collecting tibial diaphyses from 4 and 5 week-old rabbits, and followed by treating them with 0.5N HCl.Two bone defects were made in the center of the tibia of rabbits weighting 3.5 to 4 kg under intravenous anesthesia.Mesial defects were filled with demineralized bone matrix pellets (DB group), and the others were only bone defects (BC group). The bone density of the block including the bone defects was measured at 1, 2, 3, and 4 weeks nostoperatively.Using a Hologic QDR 1000, the amount of bone mineral density (BMD, g/cm2) was measured by scanning in four equal parts about 30mm in length, 10mm mesially from the distal end of the tibia, utilizing the program for the lumber spine.A cornnarison was made with the adjacent site to the bone defect as a control. Tn the first week, BMD showed low values in both DB and BC groups.In the 2nd week, BMD was higher in both groups than that of the first week, but the increase in the DB group was significant when compared with that in the BC group.In the 4th week, BMD in the DB group was similar to that of the control site.From the results of bone density measurements, dual energy X-ray absorptiometry is thought to be usetul in the evaluation of bone induction experiments.